Influenza virus-like particle vaccines made in Nicotiana benthamiana elicit durable, poly-functional and cross-reactive T cell responses to influenza HA antigens - Landry, Nathalie; Pillet, Stéphane; Favre, David; Poulin, Jean-François; Trépanier, Sonia; Yassine-Diab, Bader; Ward, Brian J. (Clinical immunology (Orlando, Fla.), 2014)
Cell-mediated immunity plays a major role in long-lived, cross-reactive protection against influenza virus. We measured long-term poly-functional and cross-reactive T cell responses to influenza hemagglutinin (HA) elicited by a new plant-made Virus-Like Particle (VLP) vaccine targeting either H1N1 A/California/7/09 (H1) or H5N1 A/Indonesia/5/05 (H5). In two independent clinical trials, we characterized the CD4+ and CD8+ T cell homotypic and heterotypic responses 6months after different vaccination regimens. Responses of VLP-vaccinated subjects were compared with placebo and/or a commercial trivalent inactivated vaccine (TIV:Fluzone™) recipients. Both H1 and H5 VLP vaccines elicited significantly greater poly-functional CD4+ T cell responses than placebo and TIV. Poly-functional CD8+ T cell responses were also observed after H1 VLP vaccination. Our results show that plant-made HA VLP vaccines elicit both strong antibody responses and poly-functional, cross-reactive memory T cells that persist for at least 6months after vaccination. •The plant-made influenza VLP vaccine platform has many potential advantages.•Benefits include cost-of-goods, scalability and speed of production.•VLP vaccination elicited durable H5 and H1 humoral and cellular responses.•T cell responses elicited by HA VLP were poly-functional and cross-reactive.•Both H1 and H5 VLP induced long-term memory CD4+ IFN-γ− IL-2+ TNF-α+ cells.